Ocean Physicochemistry versus Climate Change - Góralski, Bogdan (2014)
It is the dwindling ocean productivity which leaves dissolved carbon dioxide in the seawater. Its solubility is diminished by the rise in ocean water temperature (by one degree Celsius since 1910, according to IPCC). Excess carbon dioxide is emitted into the atmosphere, while its growing concentration in seawater leads to ocean acidification. Ocean acidification leading to lowering pH of surface ocean water remains an unsolved problem of science. My today’s lecture will mark an attempt at proving that this is a regular phenomenon in the ocean history linked to changes in the Earth’s climate. Bogdan Góralski